PELATIHAN WIRAUSAHA BAGI WARGA BINAAN LAPAS PEMUDA KELAS IIA DI KOTA TANGERANG - Hendra Hendra; Marselia Purnama; Vivin Hanitha; Octavianti Purnama; Ignasius Irvan; Tri Angreni; Donny Yana; Rini Novianti; Sonny Santosa; Kiki Kiki; Jessica Jessica; Sunny Sunny (Yayasan Education and Social Center, 2021)
The correctional system is a series of criminal law enforcement units. Inmates are not only objects but also subjects who are no different from other humans who at any time can make mistakes or make mistakes that can be subject to criminal sanctions. The Indonesian penitentiary system is more focused on the aspect of fostering prisoners. The assisted residents have the right to obtain information and obtain proper education and training which can be used as capital in the future when they return to the community. Community service activities that will be carried out in the form of training are theoretical presentations that are carried out face-to-face on the concept of entrepreneurship and business including managing marketing and finance in accordance with the needs of the inmates with a business strategy to start a business with a minimum capital, and the Dropship System. The implementation of this Community Service was carried out on October 2, 2021, taking place at the Class IIA Youth Prison, Tangerang. Buddhi Dharma University offers entrepreneurship training programs and starting a business with minimal capital and how to market products that will be sold through the dropship system and how to market them through E-Commerce media, as well as how to record financial books using the bookkeeping application for the inmates when they return to the community later